(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
Performance measurement is the basis of management with regard to controlling activities of an enterprise. Development of appropriate indicators and measurement techniques lead to many problems. The majority of enterprises begin to evaluate the efficiency, by the implementation of financial indicators that are practically incalculable. Only at a later stage, are measures used that are related to the specific problems and priorities of the process at the operational level. As a result, in most cases there is an inconsistency or it is almost impossible to manage the measurement system, which can lead to the opposite of the desired effect, and hence to a deterioration of efficiency. In order to create a coherent system of performance measures, the cause and effect at different levels of business management need to be linked. Controlling activities which are aimed at ensuring enterprise efficiency in terms of assumed goals can be helpful. The close link between strategic and operational levels enables deviation analysis of individual values of the plan at the tactical level and operational level. The compatibility of activities is evaluated on the basis of identifying strategic objectives that need to be transposed to the operational level. This article presents the problem of transposing the strategic objectives of the supply process to performance measures at the operational level and proposal of an indicator system of supply efficiency at the operational level. The main research problem of this article is to propose and develop a system of indicators and metrics of evaluation efficiency in the supply process. Keywords: Efficiency, operational controlling, supply efficiency, performance measurement